Analyzing Reading Strategies of The Second Semester Students at English Literature Study Program - Febrimarini Sinulingga (Prodi Sastra Inggris UKI, 2022)
Abstract One of the skills that students should always work to develop is reading. The success of students’ academic careers depends on their ability to gain information from reading passages. This study is based on a study that was conducted on the second semester students at the English Literature Study Program, Universitas Kristen Indonesia. It is to analyze their reading strategies. The design of this study was descriptive qualitative which was conducted through analyzing the questionnaire that distributed to the students. The participants engage in this study are six students in the second semester of English Literature UKI of regular afternoon students from employee and transfer classes program. Because most students in the afternoon regular class are workers who are also students, it is not as large as the morning regular class. Findings suggest that most of the students aware of the importance of reading strategies and already familiar with some of them. It is hoped that the study can help the students get better understanding their current knowledge about reading strategies and they can take action to improve their reading skill. The result also may help the lecturer determine the appropriate reading strategies to implemented in class. Keywords: reading strategies, KWL, previewing, story mapping, skimming and scanning Abstrak Membaca merupakan salah satu keterampilan yang selalu perlu ditingkatkan oleh siswa. Keberhasilan akademik siswa tergantung pada kemampuan mereka untuk mendapatkan informasi dari bacaan. Penelitian ini didasarkan pada mahasiswa semester dua di Program Studi Sastra Inggris, Universitas Kristen Indonesia. Penelitian ini dilakukan untuk menganalisis strategi membaca mereka. Rancangan penelitian ini menggunakan deskriptif kualitatif yang dilakukan melalui analisis terhadap angket yang dibagikan kepada pada mahasiswa. Partisipan yang terlibat dalam penelitian ini adalah enam mahasiswa semester dua UKI Sastra Inggris mahasiswa reguler sore dari kelas karyawan dan alih program. Karena sebagian besar siswa kelas reguler siang adalah pekerja yang juga mahasiswa, maka jumlahnya tidak sebesar kelas reguler pagi. Temuan menunjukkan bahwa sebagian besar siswa menyadari pentingnya strategi membaca dan sudah terbiasa dengan beberapa strategi membaca. Diharapkan penelitian ini dapat membantu siswa untuk lebih memahami pengetahuan mereka saat ini tentang strategi membaca dan dapat mengambil tindakan untuk meningkatkan keterampilan membacanya. Hasil penelitian ini juga dapat membantu dosen menentukan strategi membaca yang tepat untuk diimplementasikan di dalam kelas. Kata kunci: strategi membaca, KWL, pratinjau, pemetaan cerita, skimming dan scanning